The roles and controls of GATA factors in blood and cardiac development - Dobrzycki, T; Lalwani, M; Telfer, C; Monteiro, R; Patient, R (Wiley, 2019)
GATA factors play central roles in the programming of blood and cardiac cells during embryonic development. Using the experimentally accessible Xenopus and zebrafish models, we report observations regarding the roles of GATA‐2 in the development of blood stem cells and GATA‐4, ‐5, and ‐6 in cardiac development. We show that blood stem cells develop from the dorsal lateral plate mesoderm and GATA‐2 is required at multiple stages. Firstly, GATA‐2 is required to make the cells responsive to VEGF‐A signalling by driving the synthesis of its receptor, FLK‐1/KDR. This leads to differentiation into the endothelial cells that form the dorsal aorta. GATA‐2 is again required for the endothelial‐to‐haematopoietic transition that takes place later in the floor of the dorsal aorta. GATA‐2 expression is dependent on BMP signalling for each of these inputs into blood stem cell programming. GATA‐4, ‐5, and ‐6 work together to ensure the specification of cardiac cells during development. We have demonstrated redundancy within the family and also some evolution of the functions of the different family members. Interestingly, one of the features that varies in evolution is the timing of expression relative to other key regulators such as Nkx2.5 and BMP. We show that the GATA factors, Nkx2.5 and BMP regulate each other and it would appear that what is critical is the mutually supportive network of expression rather than the order of expression of each of the component genes. In Xenopus and zebrafish, the cardiac mesoderm is adjacent to an anterior population of cells giving rise to blood and endothelium. This population is not present in mammals and we have shown that, like the cardiac population, the blood and endothelial precursors require GATA‐4, ‐5, and ‐6 for their development. Later, blood‐specific or cardiac‐specific regulators determine the ultimate fate of the cells, and we show that these regulators act cross‐antagonistically. Fibroblast growth factor (FGF) signalling drives the cardiac fate, and we propose that the anterior extension of the FGF signalling field during evolution led to the recruitment of the blood and endothelial precursors into the heart field ultimately resulting in a larger four chambered heart. Zebrafish are able to successfully regenerate their hearts after injury. To understand the pathways involved, with a view to determining why humans cannot do this, we profiled gene expression in the cardiomyocytes before and after injury, and compared those proximal to the injury with those more distal. We were able to identify an enhancement of the expression of regulators of the canonical Wnt pathway proximal to the injury, suggesting that changes in Wnt signalling are responsible for the repair response to injury.